YOUTH AND ADULT EDUCATION (EJA) AND CURRICULUM IN BRAZILIAN STRICTO SENSU RESEARCH: A SYSTEMATIC REVIEW IN THE BDTD (2000-2024) - de Toledo, Marcelo Penteado; Amaral, Carmem Lúcia Costa; Pire, Margareth Polido (Seven Editora, 2025)
Youth and Adult Education (EJA) constitutes a foundational field in Brazil, but it is historically marked by the insufficiency of specific pedagogical resources and practices, demanding a curriculum that dialogues with the diversity and trajectories of its subjects. Considering the imperative to understand the scientific basis supporting this modality, this work focuses on the articulation between EJA and Curriculum in Brazilian research. It aims to map the Stricto Sensu academic production, systematize the temporal evolution, and identify the thematic axes incident in the field. To this end, we proceed to the systematic literature review in the Brazilian Digital Library of Theses and Dissertations (BDTD), analyzing a corpus of 136 works published between 2000 and 2024. In this way, it is observed that there is an exponential growth in production, with a significant concentration in the Southeast-Northeast axis, and that research is polarized around three axes: the Integrated Curriculum/PROEJA, the tension between Prescribed versus Lived Curriculum, and the Critical-Emancipatory Foundation. Which allows us to conclude that the field is consolidated and expanding, driven by the persistent pursuit of a politically engaged and methodologically adaptable curriculum for the specificities of EJA. DOI: https://doi.org/10.56238/sevened2025.038-063